2019
DOI: 10.1111/mmi.14175
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of tail‐anchored proteins to Trichomonas vaginalis hydrogenosomes

Abstract: Summary Tail‐anchored (TA) proteins are membrane proteins that are found in all domains of life. They consist of an N‐terminal domain that performs various functions and a single transmembrane domain (TMD) near the C‐terminus. In eukaryotes, TA proteins are targeted to the membranes of mitochondria, the endoplasmic reticulum (ER), peroxisomes and in plants, chloroplasts. The targeting of these proteins to their specific destinations correlates with the properties of the C‐terminal domain, mainly the TMD hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Additionally, we observed a large amount of the GFP signal in the vacuole, suggesting that a subpopulation of the protein was degraded in the vacuole. We concluded that, in yeast cells, HA-TA4 is mainly localized to the ER and only partially to mitochondria, contrary to the situation in T. vaginalis where it was found exclusively in hydrogenosomes [8]. This implies that the targeting signals and their decoding are not completely conserved between T. vaginalis and S. cerevisiae.…”
Section: In Yeast Cell Ta4 Localizes To the Er With An Inverted Topologymentioning
confidence: 63%
See 4 more Smart Citations
“…Additionally, we observed a large amount of the GFP signal in the vacuole, suggesting that a subpopulation of the protein was degraded in the vacuole. We concluded that, in yeast cells, HA-TA4 is mainly localized to the ER and only partially to mitochondria, contrary to the situation in T. vaginalis where it was found exclusively in hydrogenosomes [8]. This implies that the targeting signals and their decoding are not completely conserved between T. vaginalis and S. cerevisiae.…”
Section: In Yeast Cell Ta4 Localizes To the Er With An Inverted Topologymentioning
confidence: 63%
“…The obtained DNA fragments were inserted downstream of the 3xHA tag into the yeast expression vector pYX142, digested with the same restriction enzymes. To construct the pYX142-3HA-TA7 plasmid, the coding sequence for TA7 was amplified by PCR from pTagVag-2HA-TA7 [ 8 ], using primers containing the restriction sites for EcoRI and NheI. This DNA fragment was inserted downstream of the 3xHA tag of the plasmid pRS316- FIS1 pr-3HA-Fis1(cyt)- FIS1ter [ 15 ], which was digested with the same restriction enzymes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations